Tumor Microenvironment Lactate: Is It a Cancer Progression Marker, Immunosuppressant, and Therapeutic Target? - Eugene Y. Kim; Joyce Abides; Chandler R. Keller; Steve R. Martinez; Weimin Li (Molecules)
The “Warburg effect” is a term coined a century ago for the preferential use of glycolysis over aerobic respiration in tumor cells for energy production, even under aerobic conditions. Although this is a less efficient mechanism of generating energy from glucose, aerobic glycolysis, in addition to the canonical anaerobic glycolysis, is an effective means of lactate production. The abundant waste product, lactate, yielded by the dual glycolysis in a tumor, has been discovered to be a major biomolecule that drives cancer progression. Lactate is a metabolic energy source that, via cell membrane lactate transporters, shuttles in and out of cancer cells as well as cancer cell-associated stromal cells and immune cells within the tumor microenvironment (TME). Additionally, lactate serves as a pH tuner, signaling ligand and transducer, epigenetic and gene transcription regulator, TME modifier, immune suppressor, chemoresistance modulator, and prognostic marker. With such broad functionalities, the production–consumption–reproduction of TME lactate fuels tumor growth and dissemination. Here, we elaborate on the lactate sources that contribute to the pool of lactate in the TME, the functions of TME lactate, the influence of the TME lactate on immune cell function and local tissue immunity, and anticancer therapeutic approaches adopting lactate manipulations and their efficacies. By scrutinizing these properties of the TME lactate and others that have been well addressed in the field, it is expected that a better weighing of the influence of the TME lactate on cancer development, progression, prognosis, and therapeutic efficacy can be achieved.